Edukasi Literasi Digital Dalam Membentuk Perilaku Aman Berinternet pada Anak Usia Sekolah Dasar - Mufadlilah, Siti Amaliya; Riska Nisaul Mukharromah; Firdaus Siamtafa; Rokhalia Zamzami (Nawasena Bhakti, 2025)
The rapid development of digital technology has made the internet an integral part of human life, including at elementary school age. Using the internet without proper understanding can lead to risks, such as exposure to negative content, cyber bullying, and misuse of personal data. This activity aims to improve digital literacy and digital ethics in elementary school children so that they can use the internet safely. The counseling method used in this socialization activity uses a participatory approach with its implementation consisting of four stages, namely, preparation, implementation, evaluation and reporting. The results of this activity show that students can understand the importance of digital security and an increase in understanding of digital literacy from 7.0 to 9.55 points. This shows an increase in student understanding. This activity proves that digital literacy plays an important role in shaping internet safety behavior from an early age.